An Electronic Market Model with Mathematical Formulation and Heuristics for Large-Scale Book Trading - (:unkn) unknown (IEEE, 2017)
This study introduces an electronic market model for secondary book markets in which each market participant can put up books for sale, and simultaneously place requests for book purchase. The model allows participants to declare a budget limit so that for each participant, the difference between the cost of purchased books and the revenue obtained from sold books stays within the declared budget limit. The model also allows participants to declare sets of substitutable books along with their preferences so that they can purchase at most one book from each of these sets. In this study, the mathematical definition of the market model is introduced, and the corresponding winner determination problem is formulated as a multi-objective linear integer program. Since this problem is NP-Hard, three heuristic methods are proposed and the performances of these methods are demonstrated on a comprehensive test suite. The results indicate that the model can be used efficiently in large-scale electronic markets in which durable goods are exchanged with tens of thousands of participants.